Effectiveness of Angiotensin II for Catecholamine Refractory Septic or Distributive Shock on Mortality: A Propensity Score Weighted Analysis of Real-World Experience in the Medical ICU. (18th January 2022) - Quan, Michele; Cho, Nam; Bushell, Thomas; Mak, Joseph; Nguyen, Nolan; Litwak, Jane; Rockwood, Nicholas; Nguyen, H. Bryant
Abstract : Supplemental Digital Content is available in the text. Abstract : IMPORTANCE: Angiotensin II (ATII) was approved for septic or other distributive shock due to its property of increasing blood pressure within 3 hours. Limited data exist regarding its effectiveness when used in real-world clinical practice. OBJECTIVES: This study examined ATII as a third-line vasopressor based on institutional approval. DESIGN: Retrospective observational cohort study. SETTING AND PARTICIPANTS: Medical ICU at an academic tertiary care medical center. Adult patients requiring 3 or more vasopressor agents for septic shock or other forms of distributed shock from September 1, 2018, to January 31, 2020. MAIN OUTCOMES AND MEASURES: Effect of ATII after norepinephrine and vasopressin on mortality and mean arterial blood pressure response after 3 hours of administration. RESULTS: One-hundred forty-seven patients, 56 receiving ATII and 91 receiving another vasopressor (non-ATII), were enrolled. Patients in the ATII group had higher mortality compared to the non-ATII group, and more required 5 or greater vasopressor agents ( p < 0.01). After propensity score weighting, there remains a trend in higher mortality in the ATII compared to non-ATII group, but not statistically significant (86.0% vs 71.0%, p = 0.16). More patients in the ATII group continued to require 5 or greater vasopressor agents compared to the non-ATII group after propensity score weighting (45.9% vs 12.5%, p < 0.01). SOFA score was the only variable associated with mortality (OR = 1.25, 95% CI, 1.05–1.49; p = 0.01). Patients were considered a "responder" if mean arterial pressure greater than 65 mm Hg at 3 hours after the third vasopressor was initiated. Among the ATII group, 37.5% patients were responders compared to 45.1% responders in the non-ATII group (relative risk = 1.07, 95% CI, 0.6–1.93; p = 0.81). CONCLUSIONS AND RELEVANCE: Although previous data support the use of ATII due to its favorable hemodynamic response in patients with distributive shock, there was no observed benefit in mortality or hemodynamic response with ATII as a third-line vasopressor in our study of real-world patients.